Interstitial Lung Abnormalities in People With HIV Infection and Uninfected Controls. (31st January 2020) - Ronit, Andreas; Benfield, Thomas; Lundgren, Jens; Vestbo, Jørgen; Afzal, Shoaib; Nordestgaard, Børge G; Kühl, Jørgen Tobias; Kofoed, Klaus F; Nielsen, Susanne Dam; Kristensen, Thomas
Abstract: Background: Chest computed tomography (CT) findings in well-treated people with HIV infection (PWH) remain poorly characterized. Methods: Cross-sectional analysis examining interstitial chest CT findings in PWH (n = 754) and uninfected controls (n = 470). Results: HIV infection was independently associated with 1.82 (95% CI, 1.18–2.88) and 5.15 (95% CI, 1.72–22.2) higher adjusted odds of any interstitial lung abnormality and findings suspicious for interstitial lung disease, respectively. Conclusions: HIV infection was independently associated with interstitial lung abnormalities and findings suspicious for interstitial lung disease. Whether these abnormalities develop into more recognizable disease states over time is unknown but warrants further investigation. Abstract : Interstitial lung abnormalities and findings suspicious for the presence of interstitial lung disease were more frequent in people with HIV infection compared to uninfected controls and were not explained by HIV-specific risk factors.